Democratic Practices and Local Government Elections in Nigeria: Demystifying the Emerging Issues - Timothy Onimisi (International Studies Journal)
The local government administration is no doubt central to the democratic process in Nigeria. It provides the training grounds for grassroots mobilization, socio-economic development, and the cardinal philosophy of representation and political participation in the overall political system of the country. A periodic election, which is the core feature of democracy through which the people at the grassroots freely participate in the process of selection of their leaders and to ensure the legitimacy of the local government council, unfortunately, remains elusive in Nigeria. Thus, this work focuses on the reasons and implications of the near absence of local government elections in most states of Nigeria. Secondary data were used and content analysis was equally adopted for the work, while democratic participatory theory was employed. The research found that most of the state governors prefer the use of caretaker committees, which is not recognized by the constitution of the country rather than conducting a periodic election for people at the grassroots because of economic benefit and to accord themselves a political advantage over their perceived opponents. The work established that deliberate neglect of election into the local government councils, unfortunately, promotes a lack of accountability and corruption in the councils. Hence, the work recommends the amendment of the Nigerian constitution to ensure a compulsory and periodic election into local government councils, as it remains the sure means of guaranteeing democratic participation of the grassroots in the selection of the leaders.